Kesan penawaran kursus umum universiti ke atas pelajar-pelajar institusi pengajian tinggi awam dan swasta - Zarina Muhammad; Jayum Jawan; Zaid Ahmad; Normala Othman (Universiti Kebangsaan Malaysia, 2010)
﻿The aim of the study is to examine the effectiveness of general courses offered at public and private university in shaping the students skills, attitude and knowledge. The study is also try to examine if there is a significant differences between the perception of the public university student and the private university. A total of 364 UPMS final year students (representing IPTA) and 219 WITENk final year students (representing IPTS) were purposively selected for the study, Simple descriptive analysis and inference analysis were used to analyze the data. Information is gathered using questionnaires administered by the students. The finding of the study shows that the general courses offered at both the public and private universities has a high and positive impact in shaping their student skills, attitude and knowledge and yet the study finds that there is a significant differences between the level of perception of UPMS students and the level of perception of UNITEN5 students. The different is not between high and low but between high and very high.